2018
DOI: 10.1007/s11605-018-3710-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Endoscopy Reports for Esophageal Cancer Patients: Where Do We Stand?

Abstract: Detailed information on the initial endoscopic assessment is essential in today's age of multidisciplinary care. Identification and adoption of QIs for endoscopic reporting is warranted to ensure the provision of appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A study from 2018 investigated the quality of endoscopy reports for 119 patients undergoing esophagectomy due to esophageal cancer and found that only 34% of EGD reports met their criteria for “good-quality” reports. 19 Quality was higher at the specialized institution compared to other hospitals. They did not evaluate how often low-quality reports led to inappropriate surgical treatment.…”
Section: Discussionmentioning
confidence: 90%
“…A study from 2018 investigated the quality of endoscopy reports for 119 patients undergoing esophagectomy due to esophageal cancer and found that only 34% of EGD reports met their criteria for “good-quality” reports. 19 Quality was higher at the specialized institution compared to other hospitals. They did not evaluate how often low-quality reports led to inappropriate surgical treatment.…”
Section: Discussionmentioning
confidence: 90%
“…For example, an esophageal mass that begins at 18 cm from the incisors has very different treatment indications that one arising at 28 cm or one at 40 cm. 3…”
Section: Anatomic Landmarksmentioning
confidence: 99%